Electronic and magnetic behavior of 2D metals structures Y on Li(110) surface - Bo, Maolin (2021)
We investigated the bond, electronic and magnetic behavior of adsorption Yttrium atoms on Lithium (110) surface using a combination of Bond-order-length-strength(BOLS) correlation and density-functional theory(DFT). We found that adsorption Y atoms on Li(110) surfaces form two-dimensional (2D) geometric structures of hexagon, nonagon, solid hexagonal, quadrangle and triangle. The consistent with the magnetic moment are 6.66μB, 5.54μB, 0.28μB, 1.04μB, 2.81μB, respectively. In addition, this work could pave the way for design new 2D metals electronic and magnetic properties.